2021
DOI: 10.1155/2021/3913601
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Microstructure, Mechanical, Thermal, and Tribological Behavior of Cu-MWCNT Composites Processed by Powder Metallurgy

Abstract: Copper (Cu) metal matrix composite (MMC) was developed with multiwall carbon nanotubes (MWCNT) as reinforcement by using powder metallurgy (PM) technique. The composition of the composites is Cu, Cu-4 wt% MWCNT, Cu-8 wt% MWCNT, and Cu-12 wt% MWCNT. The Cu and MWCNTs were blended for 6 hours in a ball mill and compacted at a 6 ton pressure to form green compacts using a 10 ton hydraulic press. Using a tubular furnace, the heat was applied at 900°C for 1.5 hours to impart strength and integrity to the green comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Brinell hardness test was conducted to evaluate the hardness of the prepared composites [11]. This test entails pressing a hardened steel ball into the composite's surface and measuring the diameter of the resulting indentation, indicating the material's resistance to deformation or penetration by a hard object.…”
Section: Hardness Test Resultsmentioning
confidence: 99%
“…The Brinell hardness test was conducted to evaluate the hardness of the prepared composites [11]. This test entails pressing a hardened steel ball into the composite's surface and measuring the diameter of the resulting indentation, indicating the material's resistance to deformation or penetration by a hard object.…”
Section: Hardness Test Resultsmentioning
confidence: 99%
“…Thus, the hardness results emphasize the mechanical performance of ceramic coatings even more in harsh gasification environments. The elemental composition of the coated materials following their exposure to producer gas was clarified by EDAX analysis [26,27]. Erosion and structural alterations are more likely due to the higher carbon content of the gas-passed epoxy coating.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the significant difference in bulk density between Cu and CNTs is reported to cause difficulties in the mixing process of matrix and reinforcement (Zheng et al, 2022). In another study, MWCNT with a high reinforcement ratio was reported to cause agglomeration (Stalin et al, 2021). This issue was explained in the section on microstructure evaluation by drawing attention to the SEM images in Figure 2.…”
Section: Porosity and Hardnessmentioning
confidence: 97%